Exosome-based tumor antigens–adjuvant co-delivery utilizing genetically engineered tumor cell-derived exosomes with immunostimulatory CpG DNA. (December 2016) - Morishita, Masaki; Takahashi, Yuki; Matsumoto, Akihiro; Nishikawa, Makiya; Takakura, Yoshinobu
Abstract: For cancer immunotherapy via tumor antigen vaccination in combination with an adjuvant, major challenges include the identification of a particular tumor antigen and efficient delivery of the antigen as well as adjuvant to antigen-presenting cells. In this study, we proposed an efficient exosome-based tumor antigens-adjuvant co-delivery system using genetically engineered tumor cell-derived exosomes containing endogenous tumor antigens and immunostimulatory CpG DNA. Murine melanoma B16BL6 cells were transfected with a plasmid vector encoding a fusion streptavidin (SAV; a protein that binds to biotin with high affinity)-lactadherin (LA; an exosome-tropic protein) protein, yielding genetically engineered SAV-LA-expressing exosomes (SAV-exo). SAV-exo were combined with biotinylated CpG DNA to prepare CpG DNA-modified exosomes (CpG-SAV-exo). Fluorescent microscopic observation revealed the successful modification of exosomes with CpG DNA by SAV-biotin interaction. CpG-SAV-exo showed efficient and simultaneous delivery of exosomes with CpG DNA to murine dendritic DC2.4 cells in culture. Treatment with CpG-SAV-exo effectively activated DC2.4 cells and enhanced tumor antigen presentation capacity. Immunization with CpG-SAV-exo exhibited stronger in vivo antitumor effects in B16BL6 tumor-bearing mice than simple co-administration of exosomes and CpG DNA. Thus, genetically engineered CpG-SAV-exo is an effective exosome-based tumor antigens-adjuvant co-delivery system that will be useful for cancer immunotherapy. Graphical abstract: